(untitled) (International Journal of Banking and Finance, 2013)
This paper aims to begin a dialogue on how to seek a longer term solution to the sovereign debt problems in general and those of EU in particular. Although the history of debt crises is quite old, none of the several solutions proposed and tried in the past have been successful to curb recurring debt crisis. This issue has assumed critical importance as the Eurozone debt crisis, which followed after the 2007-09 global financial crisis. Several governments have been outvoted in Europe due to this crisis and the cohesion of Eurozone is at stake. A rethinking on debt creation and its macroeconomic effects are being seriously studied. It seems that traditional options available to policy makers have lost much of their luster. It is high time that unconventional measures may have to be offered for consideration to provide longer term solution. This paper is a brief on the Islamic approach to the role of debt, and has potential to limit debt creation in the long term. We present some basic tenets of that approach referring in particular to the current developed nation sovereign debt crisis.